Disaster risk reduction and innovations - Izumi, Takako; Shaw, Rajib; Djalante, Riyanti; Ishiwatari, Mikio; Komino, Takeshi (Progress in disaster science, 2019)
The Sendai Framework for Disaster Risk Reduction encourages investment in innovation and technology development in disaster risk management. However, needs for science and technology inputs are unmet, and there is a lack of policy making that is based on science and evidence. This paper identified three key issues that could help overcome these barriers: networking, coproduction of knowledge, and a stronger role played by academia.A number of innovative approaches and tools have been developed for disaster risk reduction (DRR); however, it has not yet been understood what the most effective DRR innovations are. A survey was conducted among representatives of academia, government, NGOs, and the private sector to identify the most effective DRR innovations. Community-based DRR and risk management received the most votes. Half of the top-10 list was taken up with innovative approaches, which shows that both products and approaches are widely recognized as innovations, and both contribute to the improvement of existing and traditional DRR as it tackles new challenges.To enhance the interfaces among science, technology, and policy making and the development and implementation of DRR innovations, the following is recommended: increasing coproduction with researchers and practitioners, continuing the sharing of innovation case studies, strengthening communication and dialogues among stakeholders using effective, national and local platforms, understanding that innovations are not limited to high-tech products but can be approaches as well, and pursuing research on the potential of Artificial intelligence (AI), communication tools, and innovations related to climate disaster that can improve current strategies and capacities for DRR.